Circular Warehouse Operations: ESG-Driven Optimization through Reusable Pallets - Paida, Vishweswar Rao (ExcelingTech, 2025)
Sustainability, a key concept being implemented in all aspects of commercial activities around the world, aligns with nations’ objective of transition to a greener and cleaner world. A key facet of this transition is “circular flow” or what is commonly understood as recycling. This article establishes the benefits of integrating the same principles in logistics, through a comprehensive analysis of an Environmental, Social, and Governance or ESG aligned circular warehouse model implemented across six GoBolt warehouses in North America. Combining reusable plastic pallets and Gaylords, waste compaction and corrugated recycling, and 5S-based (Sort, Set in Order, Shine, Standardize, Sustain) workflow redesign yielded an average annual savings of 54,100 per warehouse, with an estimated 139 tons per year of CO? avoided per warehouse. Additionally, there was 12% productivity enhancement due to reduced picker walking and standardized 5S practices. Comparison with benchmarks of CHEP, iGPS, IFCO, and IKEA indicates that an in-house circular model can deliver competitive carbon reductions and attractive payback periods.